Selective Copper-Catalyzed N-Arylation of Lactams with Arylboronic Acids under Base- and Ligand-Free Conditions - Bathini, Thulasiram; Rawat, Vikas Singh; Sreedhar, Bojja (Synlett, 2015)
An oxidative copper-catalyzed cross-coupling of arylboronic acids with various ring-size lactams has been developed. The N-arylated lactams were obtained in moderate to excellent yields without any additional bases, ligands, or additives. This reaction shows complete selectivity for N-arylation of lactams in the presence of a hydroxyl group.
Keywords: amides; catalysis; copper; cross-coupling; oxidation